Radio(chemo)therapy in anaplastic thyroid cancer—high locoregional but low distant control rates—a monocentric analysis of a tertiary referral center - Schmied, Matthias; Lettmaier, Sebastian; Semrau, Sabine; Traxdorf, Maximilian; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina Katrin Ursel; Iro, Heinrich; Denz, Axel; Grützmann, Robert; Fietkau, Rainer; Haderlein, Marlen (Strahlentherapie und Onkologie, 2022)
Background: Anaplastic thyroid cancer (ATC) is a lethal disease with highly aggressive disease progression. This study analyses the influence of radio(chemo)therapy, R(C)T, on disease control, survival rates and predictors for survival. Patients and methods: A total of 33 patients with ATC, treated at a tertiary referral center between May 2001 and April 2020 were included. Univariate and multivariate analysis were used to investigate correlates of R(C)T and predictors on disease control and survival rates. Results: Median follow-up was 4 months. In UICC stage IVA and IVB median overall survival (OS) was 8 months, median progression-free survival (PFS) was 6 months. Patients with UICC stage IVA and IVB and patients being irradiated with a radiation dose of more than 60 Gy showed increased OS. Of these patients, 3 were alive and free from disease. All of them receiving cisplatin-based radiochemotherapy and a minimum radiation dose of 66 Gy. UICC stage IVC showed a median OS of 2.5 months and a median PFS of 1 month. Only 2 of 16 patients had local failure. Conclusion: Depending on UICC stage, RT with high radiation dose can lead to improved OS or at least higher locoregional control. A limiting factor is the high incidence of distant metastases; therefore modern systemic treatment options should be integrated into multimodal therapy concepts.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Anaplastic thyroid cancer; Chemotherapy; Multimodal treatment; Radiation dose; Radiotherapy